Mobile Apps in Retail: Determinants of Consumer Acceptance – A Systematic Review - Wohllebe, Atilla; Dirrler, Phyllis; Podruzsik, Szilárd (International Journal of Interactive Mobile Technologies (iJIM), 2020)
With the increasing relevance of smartphones, more and more companies are trying to use mobile apps for their business purposes. At the same time, the digital transformation and online trade are putting increasing pressure on the stationary retail trade. Many retailers are therefore looking for ways to use mobile apps to attract new customers or retain existing ones. With the growing number of mobile apps in the app marketplaces, the sustainable loyalty of app users is becoming an increasing challenge. For retailers, the question arises as to which determinants influence consumer acceptance of mobile apps in retail. From an initial 44,800 search results at Google Scholar, 18 scientific papers are analyzed in a qualitative synthesis by means of a systematic review based on the PRISMA schema. In general, perceived value, practical benefits and user-friendliness are identified as determinants. In addition, the importance of linking the mobile app to the stationary POS and the function of mobile apps in retail more as digital shopping assistants and less as online stores is highlighted. The retailer who publishes the app itself also plays an important role in the consumer acceptance of the app.